2022
DOI: 10.1021/acs.langmuir.2c02117
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Approach to Synthesizing a Tannic Acid (TA)-3-Aminopropyltrietoxysilane (APTES) Coating for Efficient Oil–Water Emulsion Separation

Abstract: Plant polyphenol-inspired surface modification of membranes is helpful for oil−water separation. However, the preparation of this coating is time-consuming. Herein, we introduce a rapid synthesis of the TA-APTES coating by the addition of sodium periodate (SP). The surface chemical composition and morphology of the resultant TA-APTES hybrid coatings were characterized using SEM, ATR-FTIR, and XPS. The hydrophilicity and membrane performance were investigated by the water contact angle, pure water permeability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…However, most reported plant-phenol coating strategies are based on the oxidative polymerization of plant phenols, which usually requires tens of minutes to hours. [15,16] Further, it has been reported that the rate of AgNPs generation via reduction can be accelerated by techniques such as heating, microwave irradiation, and ultraviolet radiation. [17,18] Among them, ultraviolet treatment exhibits notable advantages, such as low equipment demand and negligible impact on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, most reported plant-phenol coating strategies are based on the oxidative polymerization of plant phenols, which usually requires tens of minutes to hours. [15,16] Further, it has been reported that the rate of AgNPs generation via reduction can be accelerated by techniques such as heating, microwave irradiation, and ultraviolet radiation. [17,18] Among them, ultraviolet treatment exhibits notable advantages, such as low equipment demand and negligible impact on the substrate.…”
Section: Introductionmentioning
confidence: 99%